PERTUSSIS IN INFANTS - V. V. Krasnov; K. F. Ilyanenkov; L. R. Pavlovich; M. V. Kuzmicheva (LLC "Diagnostics and Vaccines", 2018)
We observed 209 children the first year of life, admitted to inpatient treatment with a diagnosis of whooping cough (pertussis). In 41 patients there was the need for mechanical ventilation in treatment. Presents a number of ventilator parameters and sequence of their use in whooping cough in the event of prolonged apnea. The need for vaccinoprophylaxis of pertussis is grounded.